2016
DOI: 10.3386/w22417
|View full text |Cite
|
Sign up to set email alerts
|

Bride Price and Female Education

Abstract: Udry, Glen Weyl and participants at various seminars and conferences for helpful comments. Eva Ng, Parina Lalchandani, and Poulod Borojerdi provided excellent research assistance. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 54 publications
6
95
1
Order By: Relevance
“…Another cultural practice that has received considerable attention in recent research is the practice of bride price, which is a transfer of money and/or other valuable assets that is made at marriage from the groom and/or his parents to the bride's parents. The importance of this tradition for female educational investments has recently been studied by Ashraf, Bau, Nunn and Voena (2017). Corno and Voena (2016) and Corno, Hildebrandt and Voena (2017) study the relationship between the practice of bride price, weather shocks, and age of marriage, while Lowes and Nunn (2017) examine the relationship between the value of the bride price that was paid at marriage and the wellbeing of the wife.…”
Section: Illustrations Of the Data A Ethnographic Characteristicsmentioning
confidence: 99%
“…Another cultural practice that has received considerable attention in recent research is the practice of bride price, which is a transfer of money and/or other valuable assets that is made at marriage from the groom and/or his parents to the bride's parents. The importance of this tradition for female educational investments has recently been studied by Ashraf, Bau, Nunn and Voena (2017). Corno and Voena (2016) and Corno, Hildebrandt and Voena (2017) study the relationship between the practice of bride price, weather shocks, and age of marriage, while Lowes and Nunn (2017) examine the relationship between the value of the bride price that was paid at marriage and the wellbeing of the wife.…”
Section: Illustrations Of the Data A Ethnographic Characteristicsmentioning
confidence: 99%
“…9 By matching our data based on the ethnic group of the household head with the Ethnographic Atlas (Murdock, 1967), a database that provides information on the cultural norms and practices of di↵erent tribes around the world, we found that in all the ethnic groups in our sample the bride price custom is a common practice in marital arrangements. Hence, unlike Ashraf et al (2014), we cannot exploit variation in ethic origin to isolate the e↵ect of bride price on outcomes. Thus, we will rely on our structural model to disentangle the role of bride price from that of the economic costs associated with raising a daughter.…”
Section: [Insert Table 1]mentioning
confidence: 99%
“…Tertilt (2005) and Tertilt (2006) study the relationship between polygyny, often associated with bride price, and growth. In a recent paper, Ashraf et al (2014) show that bride price plays an important role in women's educational attainment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Chile, Kaufmann et al (2013) find that young women entering an elite education programme tend to marry more successful spouses, with various implications in terms of income and fertility. 21 In Indonesia and Zambia, Ashraf et al (2016) show how female education is used by parents as a strategy to increase the bride price on the marriage market. Higher levels of education should therefore be viewed as the result of a strategic decision to strengthen one's position on the marriage market and in future household decisions.…”
Section: Endogenous Outside Optionsmentioning
confidence: 99%